Efektivitas Art Therapy Menggambar untuk Menurunkan Kecemasan pada Remaja yang Tinggal di Panti Asuhan - Fairuz, Farah; Satriadi, Sendi (Universitas Muhammadiyah Purwokerto, 2024)
Adolescent who live in orphanages face many problems, especially the most dominant ones, namely the transition to residence, how to socialize and behave. Teenager who live in orphanages have different backgrounds, from poor economic conditions to parents who have died. The aim of this research is to determine the effectiveness of art therapy in reducing anxiety in adolescent living in orphanages. This research uses a quasi experimental method with a pre - post test approach with control group design. The number of samples in this study were 16 teenagers who lived in an orphanage. Analysis using dependent t test data and independent t test. Paired sample t-test DASS in the intervention group, the results obtained with a P value of 0.000. Paired sample t-test DASS in the control group, the result obtained with a P value 0.017. Independent t-test of pre anxiety based on DASS in the intervention and control groups, the results obtained with a P value of 0.091. Independent t-test of post anxiety based on DASS in the intervention and control groups, the results obtained with P value 0.000. This indicates that there was a very significant change before and after the intervention in terms of anxiety.